In Defense of a Category-Based System for Unification Admissions - Lindauer, Matthew (Journal of moral philosophy, 2018)
Liberal societies typically prefer relatives and spouses of their members over other prospective immigrants seeking admission. Giving this preferential treatment to only certain categories of relationships requires justification. In this paper, I provide a defense of a category-based system for “unification admissions,” non-members seeking admission for the purpose of living in the same society with members on a stable basis, that is compatible with liberalism and, in particular, does not violate the requirement of liberal neutrality. This defense does not commit liberal theorists to the traditional state sovereignty view on immigration, according to which societies have wide latitude to exclude immigrants as they see fit, and shows that, contra Ferracioli, societies are not required to treat relatives, spouses, friends, and creative partners of their members on a par in matters of immigration policy.